2007
DOI: 10.1203/pdr.0b013e318053664c
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic Preconditioning Reverses Protection After Neonatal Hypoxia-Ischemia in Glutathione Peroxidase Transgenic Murine Brain

Abstract: ABSTRACT:The effect of hypoxic preconditioning (PC) on hypoxic-ischemic (HI) injury was explored in glutathione peroxidase (GPx)-overexpressing mice (human GPx-transgenic [hGPx-tg]) mice. Six-day-old hGPx-tg mice and wild-type (Wt) littermates were preconditioned with hypoxia for 30 min and subjected to the Vannucci procedure of HI 24 h after the PC stimulus. Histopathological injury was determined 5 d later (P12). Additional animals were killed 2 h or 24 h after HI and ipsilateral cerebral cortices assayed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
29
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 36 publications
1
29
1
Order By: Relevance
“…In various animal models, a short period of hypoxia (preconditioning) may prevent ischemia-or stroke-related brain injury (33)(34)(35). To our knowledge, we provide the first evidence prenatal hypoxic preconditioning induces down-regulation of specific glutamate-receptor subunits, leading to a neuroprotective effect also detectable after pharmacological inhibition of NR2B subunit.…”
Section: Discussionmentioning
confidence: 82%
“…In various animal models, a short period of hypoxia (preconditioning) may prevent ischemia-or stroke-related brain injury (33)(34)(35). To our knowledge, we provide the first evidence prenatal hypoxic preconditioning induces down-regulation of specific glutamate-receptor subunits, leading to a neuroprotective effect also detectable after pharmacological inhibition of NR2B subunit.…”
Section: Discussionmentioning
confidence: 82%
“…86 Several other distinct characteristics of the immature brain, such as high oxygen consumption, higher iron levels, and lower expression of several endogenous antioxidant enzymes, contribute to the higher vulnerability of the immature brain due to the deleterious actions of free radicals. 87 However, overexpression of antioxidant enzymes does not necessarily protect the neonatal brain against H-I, as was shown for superoxide dismutase overexpressing pups, and is dependent on the balance of free radical scavenging pathways 88,89 and cell types. 90 Inflammation, the third major contributor to neonatal brain injury can induce neuronal death by itself as well as by enhancing excitotoxicity and oxidative stress through the release of cytokines, free radicals, and other toxic products or trigger release of excitotoxic molecules, including glutamate.…”
Section: Animal Models and The Underlying Mechanisms Of Perinatal Artmentioning
confidence: 91%
“…In the setting of H/I preconditioning, there is complete loss of ischemic preconditioning-induced cardioprotection in mice heterozygous for deficiency of HIF-1 α, which is associated with a 50% decrease in H 2 O 2 production in these mice [9]. In neurons, we previously showed that hypoxic preconditioning reverses protection after neonatal H/I in GPx 1 transgenic murine brain, indicating the importance of H 2 O 2 in mechanisms of hypoxic preconditioning [39]. Furthermore, generation of H 2 O 2, but not superoxide, during brief oxygen-glucose deprivation (OGD, an in vitro model of ischemia) induces preconditioning neuronal protection in mature primary cortical neurons [15].…”
mentioning
confidence: 96%
“…Preconditioning the neonatal brain with H/I before a severe H/I insult results in preservation of neurons and brain volume [16,40]. Recent studies suggest that preconditioning protection in vitro and in vivo is dependent on H 2 O 2 production [15,39]. From this study, preconditioning protection appears to be tightly correlated to the levels of H 2 O 2 present in the neurons at the time of preconditioning, suggesting that H 2 O 2 may regulate whether downstream regulators will be pro or anti-apoptotic (i.e., high levels are necrotic and pro-apoptotic, whereas low levels induce an anti-apoptotic program).…”
mentioning
confidence: 99%